Limonium ilergabonum (Plumbaginaceae), a new species from northeastern Iberian Peninsula - López-Alvarado, Javier; Cobacho, Iris; Arán, Vicente J.; Rosato, Marcela; Rosselló, Josep A.; Sáez, Llorenç (Phytotaxa, 2017)
A new species of Limonium (Plumbaginaceae), L. ilergabonum sp. nov., is described from the inland gypsum soils of the northeastern Iberian Peninsula (Flix, Tarragona province, Spain). The new species is closely related to the Iberian L. hibericum on morphological traits as assessed by multivariate ordination analysis (PCA), but it can be distinguished by the narrower leaves, inflorescence shape, and longer calyx. Limonium ilergabonum shows mixoploidy (2n = 18, 2n = 27), irregular pollen shapes, low levels of pollen stainability, and a single pollen-stigma combination morph (B type). All evidences suggest that L. ilergabonum is a polyploid relict species with an apomictic breeding system that has been originated from 2n = 18 ancestors, but to date any known extant diploid species may be suggested as a likely parental species.